Adaptation Of Novel The Witches By Roald Dahl To Graphic Novel By Penelope Bagieu - Muhammad Jati Kuncoro (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
Penelope Bagieu adapted the children's novel The Witches by Roald Dahl into a graphic novel. This novel tells of the struggle of a little boy who has been transformed into a mouse with his grandmother against a group of evil witches. Adapting a literary work into a literary work is a creative process consisting of adding, subtracting, removing, and developing so that it becomes a new work. This study aims to reveal the similarities and differences and the changes that occur. The method used is to analyze the storytelling elements between the two works by comparing the two.